The instrumental role of operant paradigms in translational psychiatric research: Insights from a maternal immune activation model of schizophrenia risk. Issue 3 (23rd March 2022) - Deane, Ashley R.; Ward, Ryan D.
Abstract : Rigorous behavioral analysis is essential to the translation of research conducted using animal models of neuropsychiatric disease. Here we discuss the use of operant paradigms within our lab as a powerful approach for exploring the biobehavioral bases of disease in the maternal immune activation rat model of schizophrenia. We have investigated a range of disease features in schizophrenia including abnormal perception of time, cognition, learning, motivation, and internal state (psychosis), providing complex insights into brain and behavior. Beyond simple phenotyping, implementing sophisticated operant procedures has been effective in delineating aspects of pathological behavior, identifying interacting pathologies, and isolating contributing mechanisms of disease. We provide comment on the strengths of operant techniques to support high‐quality behavioral investigations in fundamental neuropsychiatric research.